ГЕОМОРФОЛОГИЧЕСКИЕ ГРАНИЦЫ КАВКАЗА: МНИМЫЕ И РЕАЛЬНЫЕ - Ефремов Ю.В.; Камбарова Е.А. (My University, 2005)
Authors suggest reexamining the boundaries of the Caucasus taking into account the ideas of plate tectonics.
Keywords: 551.4.035(234.9)